Pengaruh Model Pembelajaran Somatic Auditory Visualization Intellectual (SAVI) Terhadap Kemampuan Kerja Sama Siswa Kelas V SD Negeri 0802 Tamiang - Era Mutiah; Latipa Hannum; Rizki Hamdan Saputra (Dirosah Islamiyah, 2026)
This study aimed to determine the effect of the Somatic Auditory Visualization Intellectual (SAVI) learning model on the collaborative skills of fifth-grade students at SD Negeri 0802 Tamiang. The research employed a quantitative approach with observation and test techniques used for data collection. The sample consisted of 30 students, including 13 male and 17 female students, representing the entire population. Data were analyzed using normality, homogeneity, and hypothesis tests. The results showed that students’ collaborative skills improved significantly after the implementation of the SAVI learning model. The observation results indicated that collaborative skills in the pre-test reached 46.66%, categorized as poor, while the post-test results increased to 82.50%, categorized as good. During learning activities, students demonstrated better cooperation within groups, actively participated in discussions, took responsibility for assigned tasks, and completed their work on time. The average pre-test score was 59.80, whereas the average post-test score increased to 80.93 after the application of the SAVI learning model. Furthermore, the hypothesis testing using the t-test showed that the calculated t-value (4.92) was higher than the t-table value (2.04) at a significance level of 0.05 with 28 degrees of freedom. Therefore, the alternative hypothesis was accepted, indicating a significant effect of the SAVI learning model on students’ collaborative skills.